2010
DOI: 10.1021/ac101036s
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Yersinia Using MALDI-TOF Mass Spectrometry and Chemometrics

Abstract: Yersinia are Gram-negative, rod-shaped facultative anaerobes, and some of them, Yersinia enterocolitica, Yersinia pseudotuberculosis, and Yersinia pestis, are pathogenic in humans. Rapid and accurate identification of Yersinia strains is essential for appropriate therapeutic management and timely intervention for infection control. In the past decade matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry (MS) in combination with computer-aided pattern recognition has evolved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 35 publications
(80 reference statements)
0
29
0
Order By: Relevance
“…The species Y. pestis and Y. pseudotuberculosis are highly related and have recently been proposed to represent two lineages of a single species rather than two different species. The ability of MALDI-TOF MS to discriminate between these species was investigated previously (181), with the study concluding that the technology was able to accurately identify members of each genus. Wittwer et al conducted similar experiments using a collection of 61 well-characterized Yersinia species isolates to generate a collection of spectra using the SARAMIS software package for analysis.…”
Section: The Enterobacteriaceaementioning
confidence: 99%
“…The species Y. pestis and Y. pseudotuberculosis are highly related and have recently been proposed to represent two lineages of a single species rather than two different species. The ability of MALDI-TOF MS to discriminate between these species was investigated previously (181), with the study concluding that the technology was able to accurately identify members of each genus. Wittwer et al conducted similar experiments using a collection of 61 well-characterized Yersinia species isolates to generate a collection of spectra using the SARAMIS software package for analysis.…”
Section: The Enterobacteriaceaementioning
confidence: 99%
“…Identification approach C. In the third analysis approach, the Matlabbased software solution MicrobeMS version 0.72 (24,(36)(37)(38)(39) developed at RKI was used (Matlab; The Mathworks, Inc., Natick, MA). MicrobeMS is publicly available as Matlab p-code (free of charge) and provides direct access to Bruker's raw spectral data and to spectra acquired by the Vitek MS workflow (formerly SARAMIS, bioMĂ©rieux/Shimadzu) via the mzXML data format (40).…”
Section: Maldi-tof Ms Details Of Maldi-tof Ms Measurements Are Inmentioning
confidence: 99%
“…Both species share genomic sequences and have identical 16S rRNA genes (53). As a consequence, their differentiation by MALDI-TOF MS is challenging; it has been found that differentiation can be carried out only on the basis of a single mass peak at m/z 3,065 (36,38). This peak has been assigned to a fragment of the plasmid-encoded (pPCP1) Pla protein.…”
Section: Fig 2 Oxidation Ofmentioning
confidence: 99%
“…thuringiensis or Y. pestis and Y. pseudotuberculosis frequently exceeds the discriminatory power of the rather straightforward data analytical approaches utilized by the commercial systems. As a consequence, three of the five laboratories that routinely use MALDI-TOF ICMS rely on customized in-house data analysis platforms for RG3 diagnostics, which allow the application of more sophisticated statistical algorithms (Lasch et al, 2008;Lasch et al, 2010;Wittwer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%